Analisis Implementasi Peraturan Daerah Nomor 6 Tahun 2002 Menangani Jumlah Gelandangan dan Pengemis di Kota Batam - Lu Sudirman; Shinta . (Journal of Judicial Review, 2019)
This research was conducted to find out the implementation of Regional Regulation Number 6 of 2002 in dealing with the problem of Homeless and Beggars. The high level of poverty is one of the main factors in the emergence of homeless and beggars, they are considered to disturb public order and the beauty of Batam City. Therefore, this problem must be surmounted immediately. This research uses empirical research methods, where research material is obtained directly from the facts that occur in the field. Furthermore, the Writer makes comparisons of written regulations, theories, journals obtained through library materials. Then the data analysis method used is the analysis of qualitative data by developing concepts, theories, legislation and comparisons of their implementation, then connecting with the facts that occur in the field. In this research it can be concluded that the legislation does not fully provide legal certainty if it is not supported by the correct implementation. It is very necessary for the role of law enforcement officials to overcome this problem and oversee the existence of homeless and beggars. However, supervision and guidance efforts carried out by the Social Service could not work effectively, the lack of support from the society of Batam City was also one of the obstacles. It is expected that the prevention efforts can eradicate the number of homeless and beggars so that they can improve social welfare in Batam City.